Dawat - Rabani, Ghulam (Notre Dame Karachi, 2000)
"Dawat" is an insightful Urdu book that explores the significance of invitation and hospitality in cultural and social contexts. It delves into the ethical and moral dimensions of offering and accepting invitations, emphasizing the importance of community and connection. Through engaging narratives and practical examples, the book encourages readers to foster relationships and strengthen bonds, highlighting how simple acts of kindness can enhance social harmony and personal fulfillment.